VIABLE SUPPLY CHAINS: THEORETICAL EVOLUTION AND EMPIRICAL EVIDENCE FROM THE ITALIAN FMCG SECTOR: Received: 16th February 2026, Revised: 20th February 2026, 23rd February 2026, Accepted: 09th March 2026, Date of Publication: 23rd March 2026 - Andrea Payaro; Anna Rita Papa (PEOPLE: International Journal of Social Sciences, 2026)
Over the past forty years, supply chain management has evolved from a technical–logistical discipline focused on efficiency into a dynamic and complex system oriented toward resilience, adaptability, and sustainability. This paper critically retraces the conceptual evolution of supply chains—from Lean to Agile, Resilient, Adaptive, and finally Viable Supply Chains—framing these paradigms in light of today’s volatile, uncertain, and digitalized environments. Through a narrative literature review and an empirical survey involving 112 Italian fast-moving consumer goods (FMCG) companies (245 respondents), the study investigates the adoption level of Viable Supply Chain principles across four key dimensions: end-to-end visibility, predictive capabilities through Artificial Intelligence, rapid reconfigurability, and integration of ESG criteria. Findings reveal that most firms have limited first-tier visibility, an embryonic adoption of AI (only 10.9% have pilot initiatives), and insufficient digital competences within procurement teams (44.2%). Nevertheless, 70% of firms collaborate with suppliers to reduce environmental impact, showing increasing awareness of sustainability. The study concludes that Italian FMCG firms are in a transitional phase: while recognizing the strategic importance of digitalization and sustainability, they have yet to fully embed viability into decision-making and operations. The paper contributes to the ongoing debate on the future of Supply Chain Management, advocating for a Complex-Aware Supply Chain—a system able to learn, adapt, and regenerate in highly complex contexts.